Employee turnover in a private university in Cyberjaya / Azlyn Sarafina A Hamid - A Hamid, Azlyn Sarafina (2011)
Turnover is a norm to any of the organization nowadays. Being in the challenging market world had made employees hop from one organization to another. They had various reasons as to why they decide to opt to leave for another job and organizations. Amongst the reasons of them leaving their current organization are because of the management of the current organization or its leadership and lack of work-life balance. The organization faces challenges and changes when their employees decide to leave the organization. This research aims to describe the characteristics of turnover, work-life balance and leadership as the predictors in identifying the intention of employees to leave and analyze the relationship and influence between the factors involved as to why employees eager to change their current employment. 136 of the academic and non-academic employees were involved in the research. The distributed questionnaire set consists of 61 items, using a Likert-scale questionnaire, to which, it had been divided into 4 parts; demographic background of respondent, turnover intention, leadership and work-life balance. The research shows that there are negative relationship between work-life balance and leadership with employee turnover. Descriptively, the mean value for turnover is 3.03 with a standard deviation of 0.318, whilst the mean value for work-life balance is 2.84 with a standard deviation of 0.443 and leadership is 2.71 with a standard deviation of 0.523 where based on the Likert-scale ratings, 1 = Strongly Disagree, 2 = Disagree, 3 = Agree and 4 = Strongly Agree.